Substrate binding and catalysis by ribonuclease P from cyanobacteria and Escherichia coli are affected differently by the 3′ terminal CCA in tRNA precursors - Pascual, Alberto (The National Academy of Sciences, 1999)
We have studied the effect of the 3′ terminal CCA sequence in precursors of tRNAs on catalysis by the RNase P RNA or the holoenzyme from the cyanobacterium Synechocystis sp. PCC 6803 in a completely homologous system. We have found that the absence of the 3′ terminal CCA is not detrimental to activity, which is in sharp contrast to what is known in other bacterial systems. We have found that this is also true in other cyanobacteria. This situation correlates with the anomalous structure of the J15/16 loop in cyanobacteria, which is an important loop in the CCA interaction in Escherichia coli RNase P, and with the fact that cyanobacteria do not code the CCA sequence in the genome but add it posttranscriptionally. Modification of nucleotides 330–332 in the J15/16 loop of Synechocystis RNase P RNA from GGU to CCA has a modest effect on k(cat) for CCA-containing substrates and has no effect on cleavage-site selection. We have developed a direct physical assay of the interaction between RNase P RNA and its substrate, which was immobilized on a filter, and we have determined that Synechocystis RNase P RNA binds with better affinity the substrate lacking CCA than the substrate containing it. Our results indicate a mode of substrate binding in RNase P from cyanobacteria that is different from binding in other eubacteria and in which the 3′ terminal CCA is not involved.